Seasonal variation in food availability and relative importance of dietary items in the Gambian epauletted fruit bat (Epomophorus gambianus) - Amponsah‐Mensah, Kofi (Ecol Evol, 2019)
1. The Gambian epauletted fruit bat (Epomophorus gambianus) is very common across a variety of West African habitats, but very little information is available on its feeding ecology or its contribution to ecosystem function. 2. We investigated seasonal variation in food availability and the relative importance of dietary items used by this species in a forest‐savannah transitional ecosystem. Dietary items were identified from 1,470 samples of fecal and ejecta pellets which had been collected under day roosts or from captured bats over a 2‐year period (2014–2015). 3. Plant phenology studies illustrated strong seasonal correlations between fruiting and flowering and rainfall patterns: Fruits were available throughout the year but with peaks of abundance during the rainy season, while flowers were mostly abundant during the dry season. Epomophorus gambianus bats utilized fruit and flower resources from 30 plant species. Although the plant species used depended on seasonal availability, there were clear preferences for certain species. 4. Flowers were an important food source for this fruit bat species especially during the dry season, contributing up to 79% of dietary items when fruit abundance was low. Ficus fruits were also important food item for E. gambianus, constituting over 40% of all dietary samples identified. 5. Policy implications. Our results show the importance of flowers in the diet of E. gambianus and highlight this species as an important pollinator and seed disperser, including for economically and ecologically important plant species. These findings contribute to an improved understanding of the ecological importance and potential role of this species in the forest‐savannah transition ecosystem for the development of fruit bat conservation management strategies.